Novel Thiazole-Fused [4,5-g] or [5,4-g]Quinazolin-8-ones and Their Quinazoline Analogues: Synthesis and Biological Evaluation - Nathan Broudic; Alexandra Pacheco-Benichou; Cécile Corbière; Blandine Baratte; Thomas Robert; Stéphane Bach; Hélène Solhi; Rémy Le Guével; Corinne Fruit; Thierry Besson (Pharmaceuticals)
Background/Objectives: In connection with previous work on V-shaped polycyclic thiazolo[5,4-f]quinazolin-9-one and [5,4-f]quinazoline derivatives that can modulate the activity of various kinases, the synthesis of straight thiazole-fused [4,5-g] or [5,4-g]quinazolin-8-ones and quinazoline derivatives hitherto undescribed was envisioned. Methods: An innovative protocol allowed to obtain the target structures. The synthesis of inverted thiazolo[4,5-h] and [5,4-h]quinazolin-8-one derivatives was also explored with the aim of comparing biological results. The compounds obtained were tested against a representative panel of eight mammalian protein kinases of human origin: CDK9/CyclinT, Haspin, Pim-1, GSK-3β, CK-1ε, JAK3, CLK1 and DYRK1A. Results and Conclusions: The results obtained show that the novel linear thiazoloquinazolines are not kinase inhibitors. The cytotoxicity of these newly synthesized compounds was assessed against seven representative tumor cell lines (human cancers: Huh7-D12, Caco-2, HCT-116, MCF-7, MDA-MB-231, MDA-MB-468 and PC-3). The majority of these novel molecules proved capable of inhibiting the growth of the tested cells. The 7-Benzyl-8-oxo-7,8-dihydrothiazolo[5,4-g]quinazolinones 5b and 6b are the most potent, with IC50 values in the micromolar range. None of these compounds showed toxicity against normal cells. A larger program of investigations will be launched to investigate the real potential interest of such compounds in anticancer applications.